Analyzing the Dynamics of SGD-BDT Exchange Rate: Economic and Geopolitical Perspectives - Bari, Md. Saiful; Kabir, Md. Humayun (Economics, Business, Accounting & Society Review, 2025)
This research explores the exchange rate dynamics between the Singapore Dollar (SGD) and the Bangladeshi Taka (BDT) over the past decade. In order to determine their impact, it evaluates important variables like GDP growth, inflation, trade balances, monetary policies, and geopolitical developments. The SGD has been strengthened by Singapore's strong economic stability, steady trade surpluses, and efficient government, according to an analysis of data from 2014 to 2024. In the meantime, the BDT has weakened due to Bangladesh's trade deficits, inflationary trends, and political difficulties and in addition to non-economic factors like political stability, market sentiment, and world geopolitical events, macroeconomic measures, including GDP growth, inflation, trade balances, and interest rates, also influenced exchange rate fluctuations. The analysis emphasizes that the SGD's gain over the BDT has been driven by Singapore's better GDP growth, lower interest rates and inflation, and ongoing trade surpluses. On the other hand, the BDT has been undermined by Bangladesh's reliance on imported products, trade imbalances, and political unrest. Exchange rate volatility has also increased due to worldwide disturbances like the COVID-19 epidemic and the Russia-Ukraine conflict. With an emphasis on the necessity of efficient currency risk management and the opportunities presented by trade and investment in the face of currency changes, these findings provide insightful information for investors, entrepreneurs, and policymakers.